1
$\begingroup$

I am trying to solve

Let $1 \neq \psi$ be a charachter of $\mathbb{F}_p$ and define $$G(\psi) = \sum_{x\in \mathbb{F}_p} \psi(x^2) $$ Proof that $|G(\psi)|^2 = p$.

What I tried so far:

$$|G(\psi)|^2 = G(\psi)\cdot \overline{G(\psi)} = \sum_{x\in \mathbb{F}_p} \psi(x^2) \cdot \sum_{y\in \mathbb{F}_p} \overline{\psi(y^2)} $$

And then $$ \sum_{x\in \mathbb{F}_p} \psi(x^2) \cdot \sum_{y\in \mathbb{F}_p} \overline{\psi(y^2)} = \sum_{x\in \mathbb{F}_p} \sum_{y\in \mathbb{F}_p} \psi(x^2) \psi( (y^{-1})^2) = \sum_{x\in \mathbb{F}_p} \sum_{y\in \mathbb{F}_p} \psi((xy^{-1})^2) $$

Now I believe we can say that per $x \neq 0$, we get that $$\sum_{y\in \mathbb{F}_p} \psi((xy^{-1})^2) = \sum_{u\in \mathbb{F}_p} \psi(u^2) = G(\psi)$$

Then $$\sum_{x\in \mathbb{F}_p} \sum_{y\in \mathbb{F}_p} \psi((xy^{-1})^2 = \sum_{y\in \mathbb{F}_p} \psi(0) + (p-1)G(\psi) $$ This seems like a weird result to me.

I have also not used the facts that $$ \sum_{x \in \mathbb{F}_p} \psi(x) = 0 \text{ and } \sum_{x \in \mathbb{F}_p} \psi(x)\overline{\psi(x)} = p $$

$\endgroup$
0
$\begingroup$

For the proof, which is a bit longer, see Proposition $8.2.2$ in Ireland and Rosen's book, "A Classical Introduction to Modern Number Theory". The main idea is to evaluate $$ \sum_x \psi(x)\overline{\psi(x)} $$ in two different ways.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.